PELAKSANAAN KEADILAN UPAH BAGI “PEKERJA MALAM WANITA” - Hendrawan Dendy Santoso; Unti Ludigdo; Ali Djamhuri (Jurnal Akuntansi Aktual, 2016)
Abstract:Management Accounting holds an information management financing which includes man-aging payment of wages for workers in the company. This study aims to interpret the implementation ofjustice of wage for women night workers. The purposing process using a transcendental phenomenol-ogy methodologies research. Subjects numbered five people consisting of 1 manager, 2 coordinators ofLadies Cord (LC) and 2 LC. All womens night worker that is “chosen by consumers” gets revenuesharing from the price of the service product. Each month, an accumulated earnings by LC reached IDR5.000.000,- but the wages that received by LC is still under the Local Minimum Wage Policy (UpahMinimum Kabupaten/ Kota) which is about IDR 500,000,-. This is shows the injustice of wage and theseunjustice makes workers to seek an additional income by doing some pornaction (prostitute). Compa-nies are required to formulate the appropriate and fairness labour agreement as stipulated in publicpolicy legislation.Keywords:accounting, wages, justice, transcendental phenomenology, public policy.